Sustainable environment proceedings of NERC 2022 - Deka, Deepmoni; Majumder, Subrata Kumar; Purkait, Mihir Kumar (Springer, 2023)
"This book covers topics that addresses the global environmental issues, their challenges, and mitigation strategies for sustainable development. Some of the major challenges global environment is facing currently are global warming induced climate change because of which various extreme weather events such as flood, drought, cyclone, forest fires have increased. Industrialization with urbanization and human anthropogenic activities have caused detrimental effect on the environment resulting in environmental pollution (air and water pollution), deforestation, degradation of ecosystems, soil erosion, ground water depletion, drinking water scarcity, biodiversity loss, depletion of fossil fuels, etc. Therefore, it has become utmost necessary to switch to significant lifestyle stages along with conservation of natural resources for a sustainable environment. Sustainable environment may be defined as the practice of responsibly managing natural resources and protect overall ecosystem to support health and well-being of present and future generations. One of the major environment sustainability is the use of renewable sources of energy such as solar, wind, hydroelectric, and biomass which will reduce environmental pollution and also minimize resource misuse. At the same time, crop rotation, solid waste management, water treatment, wastewater treatment are some of the sustainable practices we must carry out for a sustainable environment. Hope, the content of the book gives an overview of recent developments, knowledge gaps related to new research areas related to environment and their future prospects."
Keywords: Soziobiologie; Nachhaltigkeit; Klimaänderung; Klimaschutz; Bauwesen; General ecology and biosociology; Environmental protection. Environmental technology; Civil engineering. Building industry; Konferenzschrift -- 2022